Adhesive wettabillty of four Malaysian wood species / Kamarulzaman Nordin, Mansur Ahmad and Suhaini Ali - Nordin, Kamarulzaman; Ahmad, Mansur; Ali, Suhaini (2002)
Adhesive wettability of four Malaysian wood species namely Tualang (Koompassia excelsa), Kapur (Dryobalanops aromatica), Merbau (lnstia palembanica) and Meranti (Shorea spp.) were determined using contact angle measurement. Two resin systems; polyvinyl acetate (PVAc) and phenol resorcinol formaldehyde (PRF) were evaluated. The wetting angles with water were also determined for the four wood species for comparison purposes. As liquid wetting of wood surfaces is a function of time, this study attempts to quantify the adhesive penetration and spreading during wetting process though dynamic contact angle measurement. Generally, it was learned from this study that PRF exhibits better wettability than PVAc and should form more intimate contact with the wood surface regardless of the four species evaluated. The effect of species on wettability is closely related to the anatomical structure of the species. Merbau and Tualang exhibited greater wettability than Kapur and Meranti with low contact angle values.